BREEDING ECOLOGY OF AVIAN SPECIES IN DHAP CHAPAK RIVERINE FOREST, DERA ISMAIL KHAN, PAKISTAN - Inam Ullah; Jabbar Khan; Muhammad Shuaib Khan; Tauheed Ullah Khan; Shawana Huma; Ramsha Zahra; Abdus Sami; Muhammad Nawaz Rajpar (Journal of Animal and Plant Sciences, 2025)
The breeding ecology is a vital aspect of the reproduction of avian species, enabling them to increase their populations. Nest site selection by bird species offers insights into habitat suitability, food resource availability and distribution, and the appropriateness of breeding grounds. In the Dhap Chapak riverine forest, this study investigated the breeding ecology of eight important avian species: common mynas (Acridotheres tristis), Asian paradise-flycatchers (Terpsiphone paradisi), great egrets (Ardea alba), Indian robins (Saxicoloides fulicatus), laughing doves (Spilopelia senegalensis), little cormorants (Phalacro niger), black drongos (Dicrurus macrocercus), and black kites (Milvus migrans) between February 2022 and August 2023. A total of 62 bird nests were identified across the eight species at four sampling sites in Dhap Chapak Riverine Forest. The nesting habitats and site selection patterns were species-specific, with nests differing in shape, size, height, and material composition. Among the observed species, the laughing dove (Spilopelia senegalensis) was the most numerous (15 nests), while the Indian paradise flycatcher (Terpsiphone paradisi) was the least common (only two nests). Notably, the frequency of nests varied significantly across species and locations, with Site II exhibiting the highest nest density (21 nests). Our findings also reveal specific breeding ecology patterns for several species. For instance, the black kite (Milvus migrans) demonstrated high egg-hatching and chick-fledging success (100%), whereas the laughing dove had a lower fledging success rate of 66.67%. The nests of each species were often built in distinct tree species, such as Acacia nilotica for the black kite and Eucalyptus camaldulensis for the common myna (Acridotheres tristis), indicating preferences for particular tree types. Average egg dimensions and incubation periods significantly varied between species, contributing to the understanding of their breeding behaviors. Based on these findings, it was concluded that the Dhap Chapak Riverine Forest is an ideal habitat and breeding ground for many bird species.
Keywords: Breeding; Clutch size; Ecology; Vegetation; Riverine Forest; Fledging